2017
DOI: 10.4236/gep.2017.53011
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Characteristics of Hexavalent Chromium in the Soil Based on Batch Experiment and Their Implications to the Environment

Abstract: The objective of this experimental study was to determine the kinetics and equilibrium sorption of Cr(VI) in soils collected from Hengshui City of Hebei Province, China, based on batch experiments. The main concentration for this paper is on the effect of soil pH, solute concentration and ionic strength as the variable factors in the sorption of Cr(VI) in soils and the assessment of their implications to the environment. Atomic Absorption Spectrophotometer (AAS) was used for Cr(III) analysis; UV-VIS Spectropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Similar results were obtained in several studies that investigated the effect of ionic strength on Cr(VI) adsorption by soils. The most recent of them performed by Kwikima and Lema (2017) showed that Cr(VI) adsorption decreased with increasing ionic strength, due to the addition of KCI electrolyte solutions. Two possible facts were mentioned as reasons for the adsorption decrease.…”
Section: Effect Of Ionic Strength On Cr(vi) Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained in several studies that investigated the effect of ionic strength on Cr(VI) adsorption by soils. The most recent of them performed by Kwikima and Lema (2017) showed that Cr(VI) adsorption decreased with increasing ionic strength, due to the addition of KCI electrolyte solutions. Two possible facts were mentioned as reasons for the adsorption decrease.…”
Section: Effect Of Ionic Strength On Cr(vi) Adsorptionmentioning
confidence: 99%
“…Two possible facts were mentioned as reasons for the adsorption decrease. Firstly, the direct competition of chloride anions with Cr(VI) for the soil's oxyhydroxide surface sites and secondly the decrease in the electrostatic potential near the surface sites, which further affects the Cr(VI) surface complexation reactions (Kwikima and Lema, 2017). Azizian (1993) also reported the decrease of Cr(VI) adsorption with increasing pH using NaCl as background electrolyte.…”
Section: Effect Of Ionic Strength On Cr(vi) Adsorptionmentioning
confidence: 99%